2022
DOI: 10.3389/fnut.2022.955562
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary inflammatory index with chronic kidney disease and kidney stones in Iranian adults: A cross-sectional study within the Ravansar non-communicable diseases cohort

Abstract: Chronic inflammation plays a central role in the pathogenesis of chronic kidney disease (CKD). The association of dietary inflammatory index (DII) with CKD remains underexplored. Thus, the present study aimed to determine the association between the DII, risk of CKD, and kidney stone formation using the data from the Ravansar non-communicable diseases (RaNCD) cohort study conducted in Kermanshah, Iran. The cross-sectional study was conducted using the recruitment phase data of the RaNCD cohort study comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…DII has been validated that it can reflect the levels of systemic inflammation and closely associated with the expressions of blood inflammatory markers, including C-reactive protein (CRP), tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IL-10 ( 11 , 12 ). At present, DII has already been widely used to explore the roles of diet-induced inflammation in the occurrence and development of various diseases ( 13 15 ). Actually, our team previously conducted a cross-sectional study based on the NHANES to explore the association between DII and the risk of coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%
“…DII has been validated that it can reflect the levels of systemic inflammation and closely associated with the expressions of blood inflammatory markers, including C-reactive protein (CRP), tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IL-10 ( 11 , 12 ). At present, DII has already been widely used to explore the roles of diet-induced inflammation in the occurrence and development of various diseases ( 13 15 ). Actually, our team previously conducted a cross-sectional study based on the NHANES to explore the association between DII and the risk of coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported an association between DII and a variety of renal diseases including CKD and kidney stones by examining different epidemiologic methods and participants ( 10 , 12 , 27 , 30 ). A study based on 21,649 adult Americans reported the odds of prevalent CKD increased from 5.3% in the lowest to 9.3% in the highest DII quartile ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with research results from published studies. A cross-sectional study involving Iranian adults showed that individuals with higher DII scores had lower eGFR levels [ 10 ]. Another cross-sectional study focusing on the Iranian CKD population revealed an increased risk of advanced CKD stages in the highest DII quartile group [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research has highlighted the significance of a healthy dietary pattern in the management of CKD [ 9 ]. Consuming an anti-inflammatory diet rich in Ω-3 Polyunsaturated Fatty Acid (PUFA), vitamins and fiber has been associated with a reduced risk of proteinuria and an improvement in kidney function [ 10 ]. Conversely, the intake of nutrients generally considered pro-inflammatory, such as saturated fatty acids and sugars, is associated with an increased risk of worsening kidney function [ 11 ].…”
Section: Introductionmentioning
confidence: 99%